Connexin dynamics in the privileged wound healing of the buccal mucosa. Issue 4 (29th April 2013) - Davis, Nicola G.; Phillips, Anthony; Becker, David L.
Abstract Wound closure is fundamental to maintaining tissue homeostasis; a plethora of processes and signals must be coordinated, and gap junctions play a critical role. Some tissues exhibit privileged healing, such as buccal mucosa, repairing more rapidly, but gap junction connexin dynamics during wound healing in such tissues have not been investigated. To determine connexin changes during this rapid healing process, incisional wounds were made in the cheeks of mice and microscopically observed. We discovered that buccal mucosa wound edge keratinocytes do not form a thin tongue of migratory cells like epidermis; instead, a wedge of cells rapidly moves into the wound. The dorsal surfaces of opposing sides of the wounds then touch and join in a "V, " which subsequently fills up with cells to form a "delta" that remodels into a flat sheet. Immunostaining showed that connexin26, connexin30, and connexin43 are expressed at significantly higher levels in the buccal mucosa than the epidermis and that, unlike the skin, all three are rapidly down‐regulated at the wound edge within 6 hours of wounding. This rapid down‐regulation of all three connexins may in part underlie the rapid healing of the buccal mucosa.